Geographical Information System (GIS) in Malaysian construction industry and its application to project management in managing construction project – a literature review / Siti Sarah Mat Isa ... [et al.] - Mat Isa, Siti Sarah; Che’ Hashim, Izrahayu; Wan Ismail, Wan Norizan; Abdullah, Suzanah (2012)
Geographic information system (GIS) is a computer based tool and being used extensively to solve various engineering problems that involve the integration and analysis of large volumes of spatial and descriptive data from a variety of sources to which most of the project management software is lacking. In spite of the growing popularity, its complete potential to the construction industry has not been explored. The primary objectives of this paper are to describe GIS technology and explore potential construction applications that can benefit from the implementation of this technology. This research carried out study on the Geographical Information System (GIS) and its application to Project Management in Malaysian Construction Project. Practical considerations regarding GIS application to the construction industry are also addressed. This research is expected to investigate the views expressed by public and private sector clients, consultants and contractors which registered with their respective umbrella organizations in Malaysia. The descriptive survey method will be used, which comprised qualitative data gathering via pilot interviews and quantitative data gathering via structured questionnaires. Content analysis, multi-attribute analysis and rank correlation test will be used in the analysis of the data. The full paper will widely report the GIS application in project management for construction project and to define the benefit of GIS to the party involve in construction industry.